2008
DOI: 10.1021/tx700422h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of DNA Containing anN1-2′-Deoxyinosine-ethyl-N3-thymidine Interstrand Cross-Link: A Structural Mimic of the Cross-Link Formed by 1,3-Bis-(2-chloroethyl)-1-nitrosourea

Abstract: Interstrand cross-links, which are generated by chemotherapeutic treatment with bis-alkylating agents, exert their therapeutic effect by connecting the nucleobases of adjacent DNA strands together and represent some of the most threatening forms of damage suffered by genomic DNA. However, one of the reasons for treatment failure using these agents is due to enhanced repair of this DNA damage. The pursuit of understanding the repair of interstrand cross-links by repair systems has necessitated the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…First, synthesis was performed using a polystyrene rather than controlled-pore glass (CPG) solid-support due to the incompatibility of TEA·3HF with the latter 5. As an added precaution, the cyanoethyl protecting groups were removed using TEA as it has been observed that prolonged fluoride treatment using TBAF could lead to chain cleavage 29.…”
Section: Resultsmentioning
confidence: 99%
“…First, synthesis was performed using a polystyrene rather than controlled-pore glass (CPG) solid-support due to the incompatibility of TEA·3HF with the latter 5. As an added precaution, the cyanoethyl protecting groups were removed using TEA as it has been observed that prolonged fluoride treatment using TBAF could lead to chain cleavage 29.…”
Section: Resultsmentioning
confidence: 99%
“…The interest of ICL oligonucleotides lies in the possibility to generate substrates for a detailed study of cross-link repair in order to elucidate the mechanistic background for this phenomenon. Indeed, isolation of defined ICL adducts from natural sources in sufficient quantities for mechanistic studies remains a major problem [16] and treatment of DNA with external cross-linking reagents [17][18][19][20][21][22] typically yields complex mixtures of mono-adducts, and inter-and intrastrand cross-links with the desired ICLs are usually represented as minor fractions. [23] A variety of applications in the chemical biology area further justify the ongoing and intense research for efficient and highly sequence-specific cross-linked oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Although CENU ICL-containing oligonucleotides have been generated by treatment of oligonucleotides with BCNU [39], strategies for the efficient site-specific generation of this adducts on a larger scale have so far remained elusive. A number of BCNU-like adducts have been synthesized either by incorporation of a precursor (a chloroethyl modified thymine) that can form an ICL with a guanine residue [40] or by incorporation of crosslinked nucleotide dimer into DNA using solid-phase synthesis (Figure 1C) [4143]. This later strategy allowed the synthesis of bridges with different lengths and different structures.…”
Section: Chloro Ethyl Nitroso Urea Iclsmentioning
confidence: 99%